2008
DOI: 10.1007/s12039-008-0002-7
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-based electrochemical supercapacitors

Abstract: Graphenes prepared by three different methods have been investigated as electrode materials in electrochemical supercapacitors. The samples prepared by exfoliation of graphitic oxide and by the transformation of nanodiamond exhibit high specific capacitance in aq. H 2 SO 4 , the value reaching up to 117 F/g. By using an ionic liquid, the operating voltage has been extended to 3⋅5 V (instead of 1 V in the case of aq. H 2 SO 4 ), the specific capacitance and energy density being 75 F/g and 31⋅9 Wh kg -1 respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
448
2
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 813 publications
(464 citation statements)
references
References 19 publications
7
448
2
7
Order By: Relevance
“…At this point, graphene nanosheets can serve as the promising catalyst support because of its low-cost and large-scale production. In addition, free standing graphene sheets have large surface area, high thermal and electrical conductivity, and high mobility of charge carriers (6) (8) demonstrated that graphene could be a good candidate as an electrode in supercapacitors because the specific capacitance of the exfoliated graphene in the aqueous electrolyte was better than activated carbons and carbon nanotubes. In another work, Ruoff et al (9) showed that chemically modified graphene was incorporated into ultracapacitor test electrodes in order to increase the energy density of the packaged ultracapacitor by increasing the electrode thickness and eliminating additives.…”
mentioning
confidence: 99%
“…At this point, graphene nanosheets can serve as the promising catalyst support because of its low-cost and large-scale production. In addition, free standing graphene sheets have large surface area, high thermal and electrical conductivity, and high mobility of charge carriers (6) (8) demonstrated that graphene could be a good candidate as an electrode in supercapacitors because the specific capacitance of the exfoliated graphene in the aqueous electrolyte was better than activated carbons and carbon nanotubes. In another work, Ruoff et al (9) showed that chemically modified graphene was incorporated into ultracapacitor test electrodes in order to increase the energy density of the packaged ultracapacitor by increasing the electrode thickness and eliminating additives.…”
mentioning
confidence: 99%
“…Carbon nanomaterials have emerged as a rising star in the material science community, during the past two decades [10][11][12]. Carbon nanotubes and graphenes are also studied for the development of batteries, supercapacitors, and fuel cells [13][14][15][16][17][18][19][20]. Most of the research works on the conductive polymers composites focus on modification of the electrical properties [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…As the basic structure of all graphitic forms, graphene is a building block for carbon materials of all other dimensionalities, such as 0D fullerene, 1D nanotube, and 3D graphite. Because of its properties such as large specific surface area [20], high thermal and electrical conductivities [21], great mechanical strength [22], graphene has attracted a growing interest, founding potential applications in many fields such as nanocomposites [23], batteries [24], supercapacitors [25], nanoelectronics [26] and sensors [27], etc. These peculiar properties make graphene an excellent additive to dramatically enhance the mechanical, electrical and thermal properties of compounds [28].…”
Section: Introductionmentioning
confidence: 99%